#70: Comparing Prospectively Identified Etiologic Agents of Neonatal Sepsis in Southwest Ethiopia with WHO Empiric Antibiotic Guidelines. (26th March 2021) - Gusland, Daniele; Berhane, Melkamu; Bekele, Abinet; Woldegiorgis, Yamrot; Siraj, Dawd; Conway, James
Abstract: Background: Neonatal sepsis accounts for one third of global neonatal mortality. To improve access to treatment for neonatal sepsis, in 2015 the World Health Organization (WHO) released guidance for outpatient treatment (when referral is not possible or refused) of Possible Serious Bacterial Infection (PSBI). 1 However, studies from low and middle-income countries suggest that bacteria causing neonatal infection differ from high-income countries, with higher rates of Staphylococcus aureus, Escherichia coli, and Klebsiella species and high rates of antimicrobial resistance. For this reason, local surveillance is vital to develop local antibiograms and tailor appropriate prescribing. Methods: This is an analysis of the first 6 months of a prospective study of young infants admitted to Jimma University Hospital with PSBI. Young infants admitted to Jimma University Hospital with PSBI (defined by WHO danger signs: poor feeding, seizures, fever, lethargy, hypothermia, tachypnea, and increased work of breathing) are being recruited over a 12-month period. Blood cultures are obtained on admission, incubated in the BACTEC system and positive cultures evaluated for antibiotic susceptibility by Kirby-Bauer Disc diffusion. Primary outcomes are culture positivity, organism identification, and rates of antimicrobial resistance. Secondary outcomes include mortality rates and duration of hospital stay. The data included in this analysis were collected from March 21, 2019, through September 20, 2019. Data collection is ongoing. Results: In total, 196 infants have been enrolled with a culture positivity rate of 58%. At this time, most frequently identified organisms are Klebsiella spp. (43.4%) and Staphylococcus aureus (12.2%). Gram-negative rods represent 67.8% of the isolates and gram-positive cocci 32.2%. Less than half the isolates (44.4%) were susceptible to either first-line antibiotic (ampicillin and gentamicin). Only 17.4% of the gram-positive cocci were sensitive to oxacillin. In-hospital mortality rates for those with positive cultures approached 15% (compared with 5% for culture negative). The average hospital stay for infants with positive cultures was 13.9 days compared with 10.1 for those with negative cultures. Conclusion: Klebsiella spp. are responsible for a plurality of neonatal sepsis admissions at Jimma University Hospital. The organisms responsible for neonatal sepsis in southwest Ethiopia are highly resistant to the WHO recommended first-line antibiotics. It is possible that adoption of the WHO guidelines may be inappropriate in this population, which could be better served by tailoring empiric antibiotics to the identified organisms. Reference: 1. World Health Organization. Guideline: Managing possible serious bacterial infection in young infants when a referral is not feasible. (2015) Geneva, CH.